Disparities in inflammation between non-Hispanic black and white individuals with lung cancer in the Greater Chicago Metropolitan area - Byrne, Cecily A.; Gomez, Sandra L.; Kim, Sage; Oddo, Vanessa M.; Koh, Timothy J.; Fantuzzi, Giamila (Frontiers in Immunology, 2022)
Background: Lung cancer incidence and mortality rates are higher in Non-Hispanic Blacks (NHB) compared to Non-Hispanic Whites (NHW) in the Chicago metropolitan area, which may be related to exposure to chronic stress which may increase inflammation. Specific Aim: We investigated disparities in inflammation as measured by neutrophil to lymphocyte ratio (NLR) in individuals with lung cancer by race and by neighborhood concentrated disadvantage index (CDI). Methods: This retrospective, cross-sectional study included 263 NHB and NHW adults with lung cancer. We analyzed NLR as a continuous and categorical variable to determine degree and prevalence of inflammation. We used Mann Whitney U, t-tests, Chi square tests, linear and logistic regression models as appropriate. Results: More than 60% of subjects had inflammation (NLR ≥ 3) at lung cancer diagnosis. The degree of inflammation was significantly lower in NHB (NLR 5.50 + 7.45) compared to NHW (NLR 6.53 + 6.53; p=0.01) but did not differ by neighborhood CDI. The prevalence of inflammation (NLR ≥ 3) was significantly lower in NHB (55.07%) compared to NHW (71.20%; p<0.01) and in those from the most disadvantaged (54.07%) compared to the least disadvantaged (71.88%; p<0.01) neighborhoods. Conclusion: At lung cancer diagnosis, there is a lower degree and prevalence of inflammation in NHB compared to NHW, and lower prevalence in those residing in the most disadvantaged neighborhoods. Further research is needed to determine mechanisms of inflammation that may be contributing to lung cancer disparities as well as whether NLR is an appropriate biomarker when examining racial differences in inflammation.